Corpopaisagem: dança e experimentações urbanas - Marcelle Ferreira Louzada (2010)
This thesis essays to provide a perspective on dance in urban context, appropriating conceptual tools of Gilles Deleuze and Félix Guattari. Using cartography as a methodological reference and the dialogue with urban tryouts, we seek to describe the predictabilities and possibilities city offers. Belo Horizonte, which has served as a research reference, is described from its historical, political and artistic inscriptions. The research, however, could be expanded to other cities, since they maintain certain standards that connect them in a kind of conductor thread. The research moves from a deep theoretical view to urban tryouts, conceiving desire as an impulse to production of public life. By cartography, it was found that artistic proposals wished as urban interventions give other quality to the space, transforming it. Through involvement with dance tryouts on urban space it was also possible to develop a dramaturgy entitled Corpopaisagem. It is a dance practice that seeks to relate body and urban landscapes, in a composition that happens in the action instant. Corpopaisagem is thought as an improvisation exercise that offers other aesthetic possibilities to occupy urban space, from a body seen as a device.